0211 Odds Ratio Product: A Measure of Sleep Homeostasis Following Prolonged Wakefulness. (27th April 2018) - Kuna, S T; Tanayapong, P; Maislin, G; Staley, B; Pack, F M; Pack, A I; Younes, M
Abstract: Introduction: Odds ratio product (ORP) is a continuous index of sleep depth derived from the relation of EEG powers in different frequency ranges to each other. It ranges from 0 (pattern only occurring during sleep) to 2.5 (pattern only occurring during wakefulness or in arousals). An ORP of 1.25 indicates a pattern with an equal probability of occurring during wakefulness or sleep. ORP has shown excellent correlation with arousability. Sleep deprivation triggers a homeostatic response in subsequent recovery sleep. We further characterized the properties of ORP by assessing its response on recovery sleep following prolonged sleep deprivation. Methods: 202 adults (mean age 28.1 ± 7.5 years; mean BMI 24.1 ± 4.3 kg/m 2 ) with apnea-hypopnea and periodic limb movement indices <5 events/hr performed polysomnograms before and following a 36-hr sleep deprivation. ORP values from C3 and C4 signals were generated at 3-s intervals and averaged over NREM sleep (ORPNR ). To assess the effects of sleep deprivation on ORP, we compared ORPNR in each participant on the baseline and recovery nights. Results: Compared to baseline values, ORPNR decreased in recovery sleep in 189 subjects (94%) (mean±SD 0.57 ± 0.17 vs. 0.84 ± 0.20 (p =1E-54). An increase in delta and theta (collectively 0.33–6.3 Hz) powers, the conventional indicators of increased sleep pressure following sleep deprivation, occurred in 146 (72%) and 178 (88%), respectively. Beta power (16–35 Hz) decreased in 176 subjects (87%) during the recovery night. Subjects who had the highest ORP at baseline (lighter sleep) had the highest ORP during recovery, and vice versa (r=0.62; p=2E-22). Conclusion: The decrease in ORP on recovery sleep following sleep deprivation provides further strong evidence that ORP is a clinically useful measure of sleep depth. The apparent increase in sensitivity of ORP over conventional indices of sleep depth is likely related to the fact that ORP is a more inclusive index that is influenced not only by changes in slow frequencies but also by changes in beta power, which decreased following sleep deprivation. Support (If Any): NIH 1P01-1HL094307.